Synergistic effects of Fe2O3 supported on dendritic fibrous SBA-15 for superior photocatalytic degradation of methylene blue - Bashir, Abubakar Abdulkadir; Ros Shazuin Rayyanu, Mohd Zaki; Aishah, Abd Jalil; Fang Su, Jenn; Herma Dina, Setiabudi (Elsevier Ltd, 2025)
Environmental pollution caused by dye effluent has attracted much attention, and thus developing photocatalysts with superior photodegradation performance is an imperative task. A series of Fe supported on dendritic fibrous SBA-15 (Fe/DFSBA-15) catalysts with various Fe contents were prepared using a microemulsion coupled with ultrasonic-assisted impregnation methods. The findings revealed that the structural stability of DFSBA-15 was unaffected by the amount of Fe loaded. As the Fe loading increased, the size of Fe2O3 nanocrystals increased while the catalysts’ surface area decreased. The bandgap energy of the catalyst decreased with increasing Fe loading and became constant after reaching an optimal Fe loading of 10 wt%. The one-factor-at-a-time study revealed that 10Fe/DFSBA-15 degraded 94.72 % of methylene blue (MB) within 180 min at 1.5 g/L catalyst dosage, pH 8, and 10 mg/L of concentration, owing to Si-O-Fe coordination, modest Fe2O3 crystallite size, homogeneous metal distribution, slower recombination rate, and low bandgap energy. The advantageous features of 10Fe/DFSBA-15 resulted in accelerating the photodegradation rate, where 10Fe/DFSBA-15 is found as the optimal catalyst. The addition of Fe particles to the DFSBA-15 largely improved their photocatalytic activity toward MB degradation, making it a potential candidate for removing pollutants from aqueous solutions.